Topical non-steroidal immunomodulators in dermatology - Priya P Kadu (Wolters Kluwer Medknow Publications, 2023)
Immunological abnormality is the pathological basis of many dermatological disorders. Although steroids are the backbone of topical therapy in dermatology, the side effects are encountered quite frequently. Thorough knowledge of non-steroidal immunomodulators will broaden our treatment options. A summary of important non-steroidal immunomodulators has been given to help the residents understand the mechanism of action, indications, application, and adverse effects of these drugs.